MANUSIA DALAM DIMENSI TASAWUF (ISLAMIDA Journal of Islamic Studies, 2023)
Human beings are composed of physical and spiritual elements, human behavior is a manifestation and result of the movement of the soul. As an effect of the movement of the soul, human behavior always depends on the cause, namely the soul. If the soul does not exist, then physical movements including human behavior also do not exist. This research is a literature research with documentation data collection method, analysis using content analysis. The results showed that humans in the Sufism dimension have several faculties, among others 1) Active faculties that work with compulsion in one direction are called tabi'ah (Physical nature). 2) Active faculties that work with compulsion in a plurality of directions and species are called Nabati souls (An-Nafs An-Nabatiyah), 3) Active faculties that work with one goal and different self-choices that cause differences in actions that occur to them are called animal souls (An-Nafs-Alhayawaniah). 4). The active faculty that works with one goal and its own choice in unity of direction and purpose is called the angelic soul (An-Nafs Al-Malakiyah). The soul is divided into vegetative soul (al-nafs al-nabatiy-yat), sensitive soul (al nafs al hayawaniy-yat), human soul (al- nafs al-insaiy-yat), and in the division of reason there is theoretical reason (al 'aql al-nazhari), and practical reason (al-aql al-'amali).